Heterocumulene Sulfinyl Radical OCNSO. (11th January 2017) - Wu, Zhuang; Liu, Qifan; Xu, Jian; Sun, Hailong; Li, Dingqing; Song, Chao; Andrada, Diego M.; Frenking, Gernot; Trabelsi, Tarek; Francisco, Joseph S.; Zeng, Xiaoqing
Abstract: Neutral five‐atomic cumulenes formally consisting of two pseudohalogens (e.g., NCO, NNN, NSO) by sharing the central nitrogen atom are exotic species that have been barely studied. Through flash vacuum pyrolysis of CF3 S(O)NCO at ca. 1200 K, sulfinyl isocyanate, bearing resonance structures of O=C−N=S=O and O=C=N−S=O, has been generated in the gas phase and subsequently characterized in cryogenic matrices (Ar and N2 ). Its reversible conformational (syn and anti) interconversion and photodecomposition were observed.